Empowering transformation : transferable principles for intercultural planting of spiritually-healthy churches. - D-Davidson, Vee J. (Regnum Books International, 2018)
This book highlights principles related to intercultural missions, church-planting, and training of local believers, including aspects of missions praxis that challenge, modify, and/or supplement material in classic and current textbooks. The principles, which center on affirmation of dignity and empowerment of local people to bring about transformation, are re-workable in multiple settings, including those resistant to the gospel--particularly in restricted contexts or among unreached peoples where deep-rooted religious systems prevail and hostility to the gospel is prevalent.